Irrigation Water Use in the Danube Basin: Facts, Governance and Approach to Sustainability - Dogaru, Diana; Mauser, Wolfram; Balteanu, Dan; Krimly, Tatjana; Lippert, Christian; Sima, Mihaela; Szolgay, Jan; Kohnova, Silvia; Hanel, Martin; Nikolova, Mariyana; Szalai, Sandor; Frank, Anton (Journal of Environmental Geography, 2019)
In this paper we assess the irrigation water use in the Danube Basin, highlight its complexity, identify future challenges and show the relevance for a basin-wide integrative irrigation management plan as part of a more holistic and coherent resource policy. In this sense, we base our integrative regional assessments of the water-food-energy nexus on insights from an extensive review and scientific synthesis of the Danube Basin and region, experimental field studies on irrigation and agricultural water consumption, current irrigation related policies and strategies in most of the Danube countries, and regulatory frameworks on resources at European Union level. We show that a basin-wide integrative approach to water use calls for the evaluation of resource use trade-offs, resonates with the need for transdisciplinary research in addressing nexus challenges and supports integrative resource management policies within which irrigation water use represents an inherent part. In this respect, we propose a transdisciplinary research framework on sustainable irrigation water use in the Danube Basin. The findings were summarized into four interconnected problem areas in the Danube Basin, which directly or indirectly relate to irrigation strategies and resource policies: prospective water scarcity and Danube water connectedness, agricultural droughts, present and future level of potential yields, and science based proactive decision-making.